MORPHOLOGY AND HISTOLOGY OF THE SPERMATHECA OF SERINETHA AUGUR FABR. (HETEROPTERA : COREIDAE) - DHIMAN, S.C.; AHUJA, ALKA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
Spermaitheca of Serinetha augur Fabr. is differentiated into two parts, terminal spermathecal gland-cum-reservoir and coiled spermathecal duct. The former structure is a spherical sac which lies at the distal end of the duct. Histologically, it is internally lined by cuticular intima which is followed by smaller epithelial and larger secretory cells. Spermathecal duct is a long coiled tube having more thicker intima then the sac. At its distal end it possesses an elastic ring, a diaphragm and striated muscles which control the migration of spermatic fluid in and out of the spermathecal gland-cum-reservoir.